2003
DOI: 10.1124/mol.63.2.456
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evidence for Dopamine-Mediated Internalization of D2-Receptors after Amphetamine: Differential Findings with [3H]Raclopride versus [3H]Spiperone

Abstract: Competition with endogenous dopamine (DA) is usually invoked to explain changes in [11 C]raclopride binding observed after amphetamine administration in animals and humans. This account has recently been questioned because a number of inconsistencies have been reported that contradict it. In the present study, we investigated whether the decrease in [3 H]raclopride binding observed in the rat striatum after an amphetamine challenge reflects true competition with endogenous DA or agonist-mediated internalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 35 publications
1
65
1
2
Order By: Relevance
“…In interpreting this effect, it is also important to note that the competition of DA released through nicotinic activation with [ 11 C]raclopride may not be the only mechanism involved. For example, D2 receptor internalization has been proposed as a possible mechanism for the prolonged displacement of [ 11 C]raclopride after amphetamine administration (Laruelle, 2000) and a recent study has identified this as the primary mechanism in rats (Sun et al, 2003). It is therefore possible that this mechanism contributes to some extent to the reduction of BP observed in this study.…”
Section: Discussionmentioning
confidence: 62%
“…In interpreting this effect, it is also important to note that the competition of DA released through nicotinic activation with [ 11 C]raclopride may not be the only mechanism involved. For example, D2 receptor internalization has been proposed as a possible mechanism for the prolonged displacement of [ 11 C]raclopride after amphetamine administration (Laruelle, 2000) and a recent study has identified this as the primary mechanism in rats (Sun et al, 2003). It is therefore possible that this mechanism contributes to some extent to the reduction of BP observed in this study.…”
Section: Discussionmentioning
confidence: 62%
“…The SPECT measurement is performed 2 h after amphetamine administration at that moment the effect of the amphetamine administration may already be reduced. Competitive inhibition of radioligand binding is the most commonly used postulate to explain reductions in D2R binding after amphetamine administration, but other mechanisms such as dopamine D2R internalization or changes in receptor affinity could attribute as well [12,13]. To assess the ability to detect amphetamine-induced dopamine release in mice, all mice received amphetamine approximately 1 week after the baseline [ 123 I]IBZM SPECT study.…”
Section: Amphetamine-induced Dopamine Releasementioning
confidence: 99%
“…In response to the stimulation of dopamine, D 2 Rs undergo internalization in both cultured cells and brain tissue (Itokawa et al, 1996;Sun et al, 2003). To analyze whether NCAM plays a role in D 2 R internalization, we first determined the surface expression of D 2 Rs in dopamine-stimulated HEK293-D 2 R cells by a cell surface biotinylation approach.…”
Section: Ncam Reduces the Cell Surface Localization Of D 2 R And Prommentioning
confidence: 99%